The Abe restoration contemporary Japanese politics and reformation - Mark, Craig (Lexington Books, 2016)
"This book analyzes contemporary Japanese politics, charting the return of Prime Minister Shinzo Abe's domestic political dominance and his economic and foreign policy agenda. It is an up-to-date account and critique of the progress, obstacles, and far-reaching consequences of one of the most important periods in recent Japanese history"--Provided by publisher.